Igualdad y prohibición de discriminación: de 1978 a 2018 - Rey Martínez, Fernando (Revista de Derecho Político, 2017)
Resumen: A lo largo de los cuarenta años de vigencia de la Constitución de 1978, el tradicional derecho de igualdad se ha visto enriquecido por la emergencia de una nueva rama del ordenamiento jurídico: el Derecho Antidiscriminatorio. En el texto se traza la gramática conceptual de las nuevas categorías y su desarrollo jurisprudencial. El estudio analiza qué significa hoy la igualdad en sentido jurídico preciso, qué comprende la prohibición constitucional de no sufrir discriminación en general y también respecto de la igualdad entre mujeres y hombres, la igualdad étnico/racial, la igualdad de las personas con cualquier tipo de discapacidad o por motivos de orientación e identidad sexuales. Summary: 1. Sense and scope of constitutional equality 1.1 Introduction: from the classical concept of equality to new anti-discrimination law. 1.2 The legal concept of equality. 1.3 Equality in (the content) of the law and equality before (or in application) the law. 1.4 «Formal» or «legal» equality and «real» or «opportunity» equality. 1.5 Discrimination by indifferentiation. 2. Equality and prohibition of discrimination in strict sense. 2.1 Equality of Treatment. 2.1.1 Direct discrimination or treatment. 2.1.2 Indirect or impact discrimination. 2.1.3 Discrimination wrong, hidden and by association. 2.1.4 Multiple Discrimination. 2.2 Equal Opportunities: positive actions and positive discrimination. 3. Discrimination by sex / gender 3.1 Situation of the problem and regulatory framework. 3.2 Relevant jurisprudence. 4. Discrimination by ethnicity / race. 5. Discrimination for disability. 6. Discrimination by sexual orientation and identity. Abstract: Throughout the forty years of validity of the 1978 Constitution, the traditional right of equality has been enriched by the emergence of a new branch of the legal system: Anti-Discriminatory Law. The text draws the conceptual grammar of the new categories and their jurisprudential development. The study analyzes what equality means in a precise juridical sense, which includes the constitutional prohibition against discrimination in general and equality between women and men, ethnic / racial equality, equality of persons with any type of disability or for reasons of sexual orientation and identity.